Doping of SnO2 with H atoms: An alternative way to attain n-type conductivity - Stashans, A. (2016)
We propose an explanation for the origin of n-type electrical conductivity in SnO2 based on the results obtained from the DFT+U simulations. Two competitive intrinsic point defects, namely oxygen vacancy and hydrogen impurity, have been considered at different positions within the crystalline lattice in order to find out the equilibrium configurations and to analyze corresponding density of states (DOS) patterns along with the electron localization function (ELF). It has been demonstrated that hydrogen could be solely responsible for the n-type conductivity whereas the oxygen vacancy appears to have not a notable influence upon it. The computational analysis is backed up by some experimental data for undoped tin dioxide